Correlating MOF-808 parameters with mixed-matrix membrane (MMM) CO2 permeation for a more rational MMM development. Issue 21 (20th May 2021) - Thür, Raymond; Van Havere, Daan; Van Velthoven, Niels; Smolders, Simon; Lamaire, Aran; Wieme, Jelle; Van Speybroeck, Veronique; De Vos, Dirk; Vankelecom, Ivo F. J.
Abstract : Correlation of mixed-matrix membrane CO2 /N2 separation performance with the corresponding metal-organic framework (MOF) structural parameters shows that the MOF CO2 adsorption enthalpy is the best predictor of the membrane performance. Abstract : Consistent structure–performance relationships for the design of MOF (metal–organic framework)-based mixed-matrix membranes (MMMs) for gas separation are currently scarce in MMM literature. An important step in establishing such relationships could be to correlate intrinsic MOF parameters, such as CO2 uptake and the CO2 adsorption enthalpy ( Q st ), with the separation performance indicators of the MMM ( i.e. separation factor and permeability). Such a study presumes the availability of a platform MOF, which allows systematic comparison of the relevant MOF parameters. MOF-808 can take up the role of such a platform MOF, owing to its unique cluster coordination and subsequent ease of introducing additional functional molecules. For this purpose, formic acid (FA) modulated MOF-808 (MOF–FA) was post-synthetically functionalized with five different ligands (histidine (His), benzoic acid (BA), glycolic acid (GA), lithium sulfate (Li2 SO4 ) and trifluoroacetic acid (TFA)) to create a series of isostructural MOFs with varying affinity/diffusivity properties but as constant as possible remaining properties ( e.g. particles size distribution). CO2 uptake and CO2 adsorption enthalpy of the MOFs were determined with CO2 sorption experiments and Clausius–Clapeyron analysis. These MOF properties were subsequently linked to the CO2 /N2 separation factor and CO2 permeability of the corresponding MMM. Unlike what is often assumed in literature, MOF-808 CO2 uptake proved to be a poor indicator for MMM performance. In contrast, a strong correlation was observed between Q st at high CO2 loadings on one hand and CO2 permeability under varying feed conditions on the other hand. Furthermore, correlation coefficients of Q st, 15 and Q st, 30 ( Q st at 15 and 30 cm 3 (STP) g −1 ) with the separation factor were significantly better than those calculated for CO2 uptake. The surprising lack of correlation between membrane performance and CO2 uptake and the strong correlation with Q st opens possibilities to rationally design MMMs and stresses the need for more fundamental research focused on finding consistent relationships between filler properties and the final membrane performance.